Kant's political theory : interpretations and applications - Ellis, Elisabeth (University Park, Pa. : Pennsylvania State University Press, 2012)
"A collection of essays examining Immanuel Kant's lectures and minor writings as well as his political essays. Offers a comprehensive introduction to Kant's political thought from a position of engagement with modern political and philosophical questions"--Provided by publisher
Kant and the social contract tradition / Onora O'Neill -- Kant and the circumstances of justice / Arthur Ripstein -- Is Kant's rechtslehre a "comprehensive liberalism"? / Thomas W. Pogge -- Realizing external freedom: the Kantian argument for a world state / Louis-Philippe Hodgson -- The progress of absolutism in Kant's essay "what is enlightenment?" / Robert S. Taylor -- Unsocial sociability: perpetual antagonism in Kant's political thought / Michaele Ferguson -- Kant's political thought in the Prussian enlightenment / Ian Hunter -- Kant on education / Mika LaVaque-Manty -- Kant, freedom of the press, and book piracy / John Christian Laursen.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Kant, Immanuel, -- 1724-1804 -- Political and social views; Kant, Immanuel, -- 1724-1804 -- Political and social views; Kant, Immanuel, -- 1724-1804; Kant, Immanuel -- 1724-1804; PHILOSOPHY -- Political; POLITICAL SCIENCE -- History & Theory; Political and social views; Politische Philosophie; Political Science; Law, Politics & Government; Political Theory of the State